2023
DOI: 10.1097/mpg.0000000000003811
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Mucosal Inflammation in Pediatric Intestinal Failure Patients—A Unique Phenomenon

Abstract: Introduction/Objectives: As intestinal failure (IF) management improves and long-term survival rate increases, its physiological complications have become more apparent. The development of chronic intestinal inflammation resembling inflammatory bowel disease (IBD) in this population has been reported, but the literature describing it in detail is sparse. The present study was designed to characterize children with IF who developed chronic intestinal inflammation and identify the potential predispos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…As a result of lipid peroxidation, breath pentane has been shown to be positively correlated with the presence of intestinal inflammation [48]. Therefore, the increased values found in the SBS mice in our study might be a reflection of increased intestinal inflammation which is commonly found in this setting [49,50]. Isoflurane is not an endogenously produced compound but is taken up during previous anesthesia.…”
Section: Discussionmentioning
confidence: 53%
“…As a result of lipid peroxidation, breath pentane has been shown to be positively correlated with the presence of intestinal inflammation [48]. Therefore, the increased values found in the SBS mice in our study might be a reflection of increased intestinal inflammation which is commonly found in this setting [49,50]. Isoflurane is not an endogenously produced compound but is taken up during previous anesthesia.…”
Section: Discussionmentioning
confidence: 53%